Make political art. Slow writing as an investigative strategy of contingency in contemporary dance - Bertea, Francisco (Nawi, 2023)
In this paper we present a slow research and writing proposal of the political artistic doing of the independent contemporary dance group “Cantorodado”, located in the interior of the Córdoba Province (Argentina). Throughout 5 years of collaborative ethnographic fieldwork, we follow the traces of this group. We identify that the doing of this group is made of aesthetic, affective, ethical, political, economic and material agencies, which are configured relationally and contingently, where the latter is a quality of this doing. We present these findings merging narrative and vivid divergent academic writing with canonical academic writing. This approach allows us to approach the forms, rhythms and textures that contingency takes in its course. Thus, we test a methodological and writing strategy where its forms and contents communicate with the form and content of the social phenomena under study, with the intention that reading evoke the social event.
Keywords: Agenciamiento; agency; art-transformative field; divergent academic writing; collaborative ethnography